STRATEGI PEMBERDAYAAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KOTA KEDIRI - Silvirgin Latisia (Universitas Kadiri, 2019)
This study aimed to describe the strategy DinKop UMKM in empowering Micro, Small, and Medium Enterprises ( UMKM) which focused on the trade sector. In this case, the marketing mechanism which became one of the benchmarks in the development of UMKM. Moreover, empowerment conducted by DinKop UMKM should be maximized to increase the capacity of human resources in order to produce innovative products. In empowering micro, small, and medium-needed three phases which initials, participators phase, and phase emancipatory. This research method is descriptive qualitative. Data collection instruments are interviews and observations on location and also based on documents/ records/reports and legislation relating to the matter being investigated. The focus of this research is based on the initial phase, the phase of the participatory, emancipatory phase. These results indicate that the empowerment strategy DinKop UMKM in empowering Small, Mikro, and Medium Enterprises is not running optimally. Empowerment undertaken by the government in the initial phase is quite a role in providing training and counseling. The next step of participatory society and government have collaborated in developing UMKM. While the government is still constrained emancipatory phase of the provision of facilities and infrastructure in the development of UMKM.